A new Gulf security architecture prospects and challenges for an Asian role - Gupta, Ranjit; Baqadir, Abu Bakr Aḥmad; Ahmad, Talmiz; Janardhan, N. (Gerlach Press, 2014)
This book explores how growing economic ties between Asian countries and the Gulf Cooperation Council (GCC) could impact their future relationship. It postulates that the stage is now set for strategic partnerships and highlights how some Asian countries have been explicit about showcasing their power and influence in the Gulf region.